PERFORMANCE STUDY OF LiBOB/LiTFSI ELECTROLYTE SALT IN THE ALL-SOLID-STATE LITHIUM-ION BATTERY - Christin Ratri; Titik Lestariningsih; Qolby Sabrina (Jurnal Sains Materi Indonesia, 2020)
PERFORMANCE STUDY OF LiBOB/LiTFSI ELECTROLYTE SALT IN THE ALL-SOLIDSTATE LITHIUM-ION BATTERY. Solid polymer electrolyte is developed mainly to provide safer lithiumion battery upon high temperature operation. In this research, we employ LiBOB and LiTFSI electrolyte salt in various concentration to replace commercially used LiPF6 salt. Solution cast method was performed to produce polymer electrolyte membrane. PVdF-HFP was chosen as polymer matrix due to high dielectric constant, and compatibility to wide array of electrode materials as well as electrolyte salts. Higher amount of electrolyte salts contributes to thicker membrane and hence higher current output of the lithium-ion battery half-cells. SEM, FT-IR spectroscopy, and cyclic voltammetry measurement was conducted to evaluate li-ion battery cell performance. Between the two electrolyte salts used in this experiment, LiTFSI salt exhibited better performance compared to LiBOB.